The Revocation of Kashmir’s Special Status by Narendra Modi Administration in 2019 - Setyorini, Fitri Adi; Mukti, Takdir Ali (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2020)
Kashmir has a special status under Article 370 and 35A of the Indian Constitution, which granted special autonomy of Kashmir. The paper examines the reasons behind the Indian government's policy under Indian Prime Minister Narendra Modi to revoke the special status of Kashmir. The question is, why the Indian government revoked the special status of Kashmir in 2019 when the special status has been entrenched in the last 73 years ago. The objective of this research is to identify the reasons behind the Indian government's policy to revoke the special status of Kashmir. By a qualitative research, the findings show that the existence of economic interests is the background for revoking the special status of Kashmir. The research argues that the Indian business group (Taipan) as a major milestone in the success of Narendra Modi campaigns in 2014 and 2019 elections, demanding the Indian government to eliminate regulatory barriers between the center and the regions, to create a national market without any restrictions. Demands given by Taipan cause the dynamics between the central and local governments. This research is expected to assist the development of international relations in political economy studies.